Residency, Citizenship And Belonging: Choice And Uncertainty For Studentsturned-migrants In Australia - Robertson, Shanthi Kathleen (Penerbit Universiti Sains Malaysia (USM Press), 2008)
Since 1998, Australian migration policy has overtly recruited international graduates into the skilled migration stream, and evidence suggests that increasing numbers of international students are considering their study in Australia as a pathway to residency. However, the nature of the journey from student to resident as a migration process remains largely under researched, particularly in terms of the transition from transient student to permanent resident, and from permanent resident to citizen. This paper, based on in-depth interviews with students-turnedmigrants from a variety of source countries, examines the choices and strategies of these migrants in terms of applying for residency and considering naturalisation. Viewing the student-migrant experience through a transnational lens, this paper will foreground the meanings that the participants ascribe to residency, citizenship and belonging. I will consider their choices in terms of the negotiation of their belonging across multiple nations, and outline some of the challenges and uncertainties they face through this decision making process.